การประเมินคุณภาพชีวิตด้านสุขภาพในผู้ป่วยมะเร็งช่องปากไทยกลุ่มหนึ่ง - ปิยนาถ กุยสาคร (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Objectives: 1) To compare health-related quality of life in oral cancer patients before and after treatment. 2) To compare health-related quality of life between oral cancer patients and oral lichen planus patients. Materials and Methods: A modified University of Washington Quality of Life Questionnaire in Thai has four components: disease-specific items (pain, appearance, activity, recreation, swallowing, chewing, speech, shoulder, taste, saliva, mood and anxiety), importance-rating scale, general quality of life questions and opened-end questions. Oral cancer patients, Rajvithi Hospital and Faculty of Dentistry, Chulalongkorn University were interviewed on the day of hospital admission, 25-49 days post-operatively and 25-60 days post-treatment. Wilcoxon signed-rank test for matched paired, paired t-test and McNemar test were used to compare scores pre-treatment and post-treatment. Mann-Whitney U test, unpaired t-test and chi-square tests were used to compare scores of patients with oral cancer and oral lichen planus. All analyses were conducted using SPSS 11.5 for Windows at significance level 0.05. Results: Fifty-one oral cancer patients, thirty-seven were men and fourteen were women. The age range was 22-80 (mean 55.8). Ninety-four percent of patients had squamous cell carcinoma. Fifty-seven percent of patients were treated with surgery and post-operative radiation therapy. Post-operatively, oral cancer patients presented significantly poorer scores of swallowing, chewing, speech and shoulder. Post-treatment, oral cancer patients presented with significantly poorer scores of swallowing, chewing, shoulder taste and saliva. Oral cancer compared with oral lichen planus patients presented with significantly poorer scores of nearly whole domains in disease-specific items. Conclusion After treatment, oral cancer patients had significantly worse health-related quality of life scores than pre-treatment and oral cancer patients had significantly worse health-related quality of life scores than oral lichen planus patients.